Livelihood Assets of Lantebung Mangrove Ecotourism Community - Sabar, Adrayanti; Rusyid, Emban Ibnu; Diana, Fitrah; Ansar, Ansar; Annisa, Nur; Idzatilangi, Wening Ila; Agustiningrum, Chinty (Jurnal Wasian, 2023)
Encountering economic challenges, particularly in Indonesian coastal areas, has been a common occurrence for us. Particularly, the settlements situated along the seaside in isolated or disadvantaged regions. The repercussions of these issues manifest as a modification or reduction in the calibre of the coastal ecosystem. To address these issues, one possible approach is to carry out a Livelihood analysis. This strategy employs and consolidates the capital or assets possessed by the community, as delineated in the pentagonal assets model. The resulting pentagon diagram will illustrate the assets that can be enhanced or optimised to provide a balanced life for individuals. The research methodology employed is a descriptive analysis of the data collected through field observations, interviews, focus group discussions (FGDs), and documentation studies. The assessment of livelihood assets involves the evaluation of five types of capitals: human capital, natural capital, physical capital, social capital, and financial capital. These capitals are then analysed using the pentagonal assets model. The variables possessed by the five assets were quantified and subsequently categorised into high, medium, and low classifications. The findings indicated that the Lantebung mangrove ecotourism community had a satisfactory level of availability of livelihood assets. The asymmetrical shape of the resulting Pentagonal Assets is due to the unequal and imbalanced access that farmers have to the five assets. Additionally, this is due to the community's significant ownership of assets. The minimum score is 1.00, while the maximum score is 3.00. The community's social capital and physical capital have a score of 2.44 and are considered to have a high asset status. The status of human capital is moderate, with a score of 1.89, while the situation of financial capital is also moderate, with a score of 1.86. The lowest position is in natural capital, scoring 1.64.